Depletion-restitution therapy of autoimmune rheumatic diseases. Part 2. Perspectives on bispecific antibodies - A. L. Maslyanskiy; D. A. Dibrov; A. M. Lila; A. V. Torgashina; E. G. Zotkin; M. Yu. Samsonov; G. A. Togizbayev (Современная ревматология, 2025)
One of the most promising approaches to depletion-restitution therapy is the development and use of drugs based on bispecific monoclonal antibodies (bsAbs). Therapeutic bsAbs are genetically engineered biological products (biologics) based on immunoglobulin molecules capable of simultaneously binding multiple antigens, making them a promising platform for novel drugs. A specific type of such agent, which incorporates at least two antigen-binding (Fab) fragments within a single immunoglobulin molecule – one targeting a specific cell-surface receptor and the other binding and activating to the CD3ε domain of CD3 molecule of the T-cell receptor complex – has been termed a bispecific T-cell engager (BiTE).Currently, BiTE molecules that engage effector cells of the humoral immune system are the most clinically advanced subclass of bsAbs. Their ability to deplete target cells in peripheral blood and tissues has been clearly demonstrated in the treatment of resistant hematological malignancies such as B-cell precursor acute lymphoblastic leukemia, various lymphoproliferative disorders, and plasma cell dyscrasias. Recent years have seen attempts to repurpose bsAbs for the treatment of refractory, prognostically unfavorable forms of systemic autoimmune rheumatic diseases (SARDs), supported by theoretical rationale, experimental evidence, and parallels with successful CAR-T cell therapy.Beyond BiTEs, the bsAb platform also enables development of biologics with extended pharmacokinetics, multi-cytokine targeting potential for synergistic suppression of inflammation, and checkpoint-directed modulation of targeted cell functional activity.Advantages such as standardized manufacturing, off-the-shelf availability, predictable pharmacokinetics (with a known and limited half-life), flexible dosing regimens enabling slow escalation of the dose, the possibility of individualizing treatment duration and dosing frequency, the feasibility of repeated treatment cycles, the option to discontinue therapy in case of adverse events, and the significantly lower cost of short low-dose treatment cycles compared to CAR-T cell therapy – all these make bsAb-based strategies a highly attractive priority for next-generation depletion-restitution therapies for SARDs.